Political-Economic impact of growing rivalry between china and the Quad Alliance on Small states in Asia: Special Reference to Sri Lanka - Abeysinghe, Chaminda; Wijesinghe, Hashan (Technium Social Sciences Journal, 2021)
With Asia is becoming the centre of international affairs, it has also become the battle ground for world supremacy. On one hand, China has continued to exert its power on Asia, particularly using its economic might. On the other hand, to contain this growing Chinese influence, the United States, India, Japan and Australia have joined hands and formed an informal alliance, commonly known as the Quad. This rivalry between the Quad and China is expected to make a significant impact on the future of Asia. Against this backdrop, this study examines the political-economic impact of this rivalry on small states in the region with special reference to Sri Lanka. The geostrategic location of Sri Lanka has made it a major concern for all major powers. Looking at the methodology, this study is a qualitative research and a content analysis carried out using secondary data. Here, as far as the major findings are concerned, while as individual states the Quad members do not possess enough capacity to challenge China’s influence on Sri Lanka, as a single unit, they certainly a make a formidable force. From Sri Lanka’s perspective, the political-economic impact is multi-dimensional. One hand, the Quad is certain to make a great impact on the foreign policy decision making process of the country. Here however, what is important to understand is the fact that this rivalry provides small countries such as Sri Lanka with greater bargaining power. Sri Lanka has the potential to be benefitted from both the Quad as well as China.